PTU-189 Accuracy of Simtomax Rapid Coeliac Screening Test Compared with Elisa TTG Assay and Duodenal Biopsy. (4th June 2013) - McClements, D; Rivera-Forrester, R; Horsted, F; Murphy, C; Probert, C; Subramanian, S
Abstract : Introduction: Point-of-care testing kits are now available for coeliac disease (CD). Simtomax® is a rapid screening test which detects IgA deficiency as well as IgA and IgG antibodies to deamidated gliadin peptide (DGP). We evaluated the performance of the Simtomax® rapid screening test for CD against routine lab ELISA tTG testing and histologically confirmed CD. Methods: A retrospective study of 191 patients who underwent CD serological testing at the Royal Liverpool University Hospital was carried out. Electronic casenotes were interrogated to identify serology, endoscopy and histology results. The saved serum was tested using the Simtomax® test kit as per the manufacturer's instructions. Any Simtomax® test that was incongruous with ELISA or biopsy results was re-tested. Sensitivity, specificity, positive predicitive values (PPV) and negative predictive values (NPV) were calculated for Simtomax® and compared to histology and tTG ELISA. Results: All 191 patients underwent ELISA testing. Twenty six (13.6%) patients had positive ELISA testing; of these the Simtomax® test was positive in 20 patients and negative in 6. One hundred and sixty five (86.4%) patients had negative ELISA testing; of these Simtomax® was negative in 164 patients and positive in 1. Using ELISA as the gold standard the sensitivity of the Simtomax test was 77% (95% CI 56–90%), specificity 99% (96–99%), PPV 95% (76–99%) and NPV 96% (92–99%). Forty four patients underwent gastroscopy and duodenal biopsy. 15 patients had histological evidence of CD, of these Simtomax® test was positive in 11 patients and negative in 4; tTG ELISA was positive in all (median titre 58, range 7.8 to 80). Twenty nine patients had negative histology; of these all 29 Simtomax® tests were negative; tTG was negative in all except one patient. Using duodenal biopsy as the gold standard the sensitivity of Simtomax® was 73% (95% CI 45% > 91%), specificity 100% (85% > 100%), PPV 100% (68% > 100%) and NPV 88% (71% > 69%). No patients in the group were identified as having IgA deficiency by standard assay or Simtomax® testing. No false negative or false positive result was altered by re-testing. Conclusion: The Simtomax® testing kit has good specificity but is limited by its low sensitivity. The findings of our pilot study argue against using Simtomax® testing to screen for CD. Further large scale studies correlating tTG and Simtomax® to histology are indicated. Disclosure of Interest: None Declared.